A Doctrinal Study of the Rule of Abstaining from Disputes among the Companions - Hamood, Abdul Hameed Ahmad Murshid (Journal of Islamic and Religious Studies, 2022)
This research aims to define the rule of abstaining from disputes among the Companions, in terms of historical evidence, and the historical circumstances that produced this rule, to know the positions of scholars on this rule, to study its purposes, and effects. The study proves the ratio of this ruling to Omar bin Abdul Aziz, and that most scholars considered it obligatory; until it became a part of the creed of the predecessor. The purpose of this ruling was to cut off the path for those who advocate sedition and hatred, and to clarify the consequences of misunderstanding them, and scholars’ reluctance to realize the historical narratives mentioned in the sedition. The people having whims and grudges took precedence for it and this misunderstanding inherited ignorance among many contemporaries in dealing with the events of the sedition and prompted some of them to adopt the lies that the rejectionists and orientalists have decided. The paper recommends studying the phenomenon of intercourse between the methods of the rejectionists and orientalists about the disputes among the Companions, and immunization of the society from the suspicions about the Companions through modern media.